2013
DOI: 10.1890/12-1472.1
|View full text |Cite
|
Sign up to set email alerts
|

Management trade‐off between aboveground carbon storage and understory plant species richness in temperate forests

Abstract: Abstract. Because forest ecosystems have the capacity to store large quantities of carbon (C), there is interest in managing forests to mitigate elevated CO 2 concentrations and associated effects on the global climate. However, some mitigation techniques may contrast with management strategies for other goals, such as maintaining and restoring biodiversity. Forest thinning reduces C storage in the overstory and recruitment of detrital C. These C stores can affect environmental conditions and resource availabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
31
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 85 publications
6
31
0
2
Order By: Relevance
“…Such an approach would have to include setting priorities about which features and processes are more important in the short versus long term. Treatments prescription and expectations could then be managed to account for different response patterns, trade-offs, and synergies (as highlighted in Figure 4, see also [64]). As an alternative to compromising when achieving multiple structural and compositional goals simultaneously, foresters may explore options to spatially separate specific restoration goals within stands and across the landscape.…”
Section: Discussionmentioning
confidence: 99%
“…Such an approach would have to include setting priorities about which features and processes are more important in the short versus long term. Treatments prescription and expectations could then be managed to account for different response patterns, trade-offs, and synergies (as highlighted in Figure 4, see also [64]). As an alternative to compromising when achieving multiple structural and compositional goals simultaneously, foresters may explore options to spatially separate specific restoration goals within stands and across the landscape.…”
Section: Discussionmentioning
confidence: 99%
“…As such, there were no strong trade-off between the two potentially conflicting management objectives of maintaining positive biomass increment and promoting oak regeneration. Previous studies have shown some degree of trade-offs between C storage and features that might increase adaptive capacity such as structural and compositional complexity (D'Amato et al, 2011;Bradford and D'Amato, 2012;Burton et al, 2013;Seidl and Lexer, 2013), but did not specifically address regeneration as an adaptive factor. The lack of trade-offs in this study may be somewhat related to the low-intensity of management and lack of disturbance-caused mortality of overstory trees in the system.…”
Section: Discussionmentioning
confidence: 99%
“…Forest managers have expanded their objectives from traditional timber production to include broader goals of providing ecosystem goods and services (Burton et al 2013). However, the primary aims of common international and national forest protection measures regarding afforestation and reforestation are to enhance productivity and mitigate CO 2 accumulation by sequestering C. Climate change and biodiversity loss are two interrelated global crises but are independent of forest protection programme objectives launched by most national governments.…”
Section: Introductionmentioning
confidence: 99%